FREQUENCY OF CLINICAL SYNDROMES IN CHILDREN WITH CONGENITAL HEART DEFECTS ADMITTED AT TERTIARY CARE HOSPITAL - REHMAN, ZU; HAMID, M; KHAN, A; GUL, S; ALI, S; AHMAD, I; ULLAH, S (Biological and Clinical Sciences Research Journal, 2024)
Congenital Heart Disease, more commonly known as CHD, is among the most common forms of heart disease that affect children as well as adults. Objective: The study's primary purpose is to find the frequency of clinical syndromes in children with congenital heart defects admitted at tertiary care hospitals. Methods: This retrospective observational study was conducted at MMC Teaching Hospital Peshawar from January 2023 to June 2023. Data were collected from 295 patients suffering from CHD and admitted at tertiary care hospitals. Children aged 0-18 years and with confirmed diagnosis of CHDs via echocardiography, cardiac MRI, or cardiac catheterization were included in the study. Patients who underwent heart surgery before initial diagnosis at the study hospital were excluded. Data were collected from hospital records, including demographic information, clinical presentation, type of congenital heart defect, associated clinical syndromes, and comorbidities. Results: Data were collected from 295 patients. Patients with congenital heart defects (CHDs) were young children, with 64.4% aged between 0 to 5 years. There was a slight male predominance, accounting for 54.2% of the patients. Cyanosis was most prevalent in patients with Tetralogy of Fallot (77.8%), while heart failure was commonly observed in those with Ventricular Septal Defect (44.4%) and Coarctation of the Aorta (50.0%). Growth retardation was significantly associated with Tetralogy of Fallot (44.4%) and Ventricular Septal Defect (27.8%). Conclusion: It is concluded that children with congenital heart defects experience a high frequency of clinical syndromes, necessitating early diagnosis and specialized, multidisciplinary care. Tailored management strategies based on specific CHD types can significantly improve these patients' health outcomes and quality of life.